The Interpretation of Tsamanan Qalīlan in the Qur'an (A Thematic Study) - Rambe, Irpan; Dwi Rahma Zura; Meli Eliza (The Future of Education Journal, 2025)
This research is motivated by the author's interest in the frequent use of the phrase Tsamanan Qalīlan in the Qur'an. The phrase Tsamanan Qalīlan appears at least 10 times in the Qur'an, although there are 9 verses with similar meanings. Furthermore, the phrase occurs in different surahs. Tsamanan Qalīlan means "a cheap price." Therefore, the purpose of this study is to explore its interpretation in the Qur'an. This research uses a qualitative method with a library research approach. The primary sources in this study are various tafsir (interpretation) books, while secondary sources include books, articles, and scholarly writings related to the research. The analysis in this study employs content analysis. Based on the Qur'anic dictionary Mu'jam Mufahras li Alfazil Qur'an, the author found five sub-themes grouped from various verses in different surahs in the Qur'an. One of these themes is related to personal integrity, which is composed of 3 verses found in Surah Ali 'Imran and Surah An-Nahl. Another theme concerns the misinterpretation of verses, consisting of 2 verses from Surah Al-Baqarah and Surah At-Tawbah. The third theme is related to the encouragement to believe, which appears in 2 verses from Surah Al-Baqarah and Surah Ali 'Imran. The fourth theme discusses the concealment of the truth, which can be found in Surah Al-Baqarah. Finally, the fifth theme pertains to adhering to the laws given by Allah, found in Surah Al-Maidah.